2018
DOI: 10.15171/apb.2018.063
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Evaporation Drug Delivery System: Concept to Commercial Products

Abstract: Since two decades or so transdermal route established itself as better alternative to traditional oral route. This is possible due to continuous innovations in transdermal drug delivery (TDD), which not only enables researchers from academia and industry to successfully develop and launch many new pharmaceuticals but also allow to include new classes of drugs that can be developed into transdermal formulations. These successes are achieved due to the use of novel techniques based on either physical or chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Transdermal drug delivery system (TDDS) is one of the most exciting parenteral drug delivery systems in the pharmaceutical field. 1) TDDS confers several advantages such as decreasing dosing frequency, reducing side effects, and avoiding hepatic first-pass metabolism. 2,3) Despite these advantages, TDDS often has difficulty in drug permeation ability because the skin's hydrophobic stratum corneum acts as an effective barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Transdermal drug delivery system (TDDS) is one of the most exciting parenteral drug delivery systems in the pharmaceutical field. 1) TDDS confers several advantages such as decreasing dosing frequency, reducing side effects, and avoiding hepatic first-pass metabolism. 2,3) Despite these advantages, TDDS often has difficulty in drug permeation ability because the skin's hydrophobic stratum corneum acts as an effective barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lower drug concentrations incorporated into topical/transdermal SEDDSs might not be problematic [28,33]. On the other hand, supersaturated vehicles destined for topical/transdermal drug delivery have high success rates due to enhanced flux values as the high drug concentration of the vehicle establishes a driving force for drug partitioning into the skin due to maintained saturated drug concentrations at the skin surface [33,53]. Remarkably, supersaturated SEDDSs evidently rendered the inhibition of drug precipitation in a kinetic and thermodynamic fashion by slowing crystal growth together with nucleation [33].…”
Section: Active Compounds Incorporated In Seddssmentioning
confidence: 99%
“…Remarkably, supersaturated SEDDSs evidently rendered the inhibition of drug precipitation in a kinetic and thermodynamic fashion by slowing crystal growth together with nucleation [33]. Therefore, it might be more advantageous to present supersaturated SEDDSs at the skin surface compared to decreased drug concentrations [53].…”
Section: Active Compounds Incorporated In Seddssmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that penetration enhancers, particularly organic solvents and surfactants, induce different skin ailments such as contact urticaria, erythema, and burning sensation [17]. In addition, there is no report in the literature on the long-term effect of penetration enhancers on the skin and particularly on the SC [18]. Active methods use the application of external energy as driving force or by physically disrupting the SC for enhancing drug transport through skin.…”
Section: Introductionmentioning
confidence: 99%